An Analysis on Students' Grammatical Errors in Writing Degrees of Comparison - Oktya Putri Bungsu; Afrianto Daud; Masyhur Masyhur (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The objectives of this research are to analyze the types of errors which students made in writing degrees of comparison and to find out the sources of the errors. This research is a mixed-method research, which is a combination of qualitative and quantitative methods within a single research project. Using cluster sampling, 25 third grade students of MTs Masmur Pekanbaru were chosen as the sample of this research. The instruments used to get the data are written tests and semi-structured interviews. The procedure of error analysis was used to analyse the data, which are process of identification, description, explanation, and evaluation of errors. Based on the process of identification and description, it was found that students committed 365 errors that were classified into four types of error: misformation (60,27%), omission (26,58%), addition (6,85%), and misordering (6,30%). This study also revealed that the sources of the errors are: intralingual transfer (61,39%), communication strategy (17,82%), interlingual transfer (14,85%), and context of learning (5,94%). Furthermore, the errors committed by students were reconstructed into the correct form as the evaluation. Therefore, several recommendations were given to the students such as trying to explore more learning sources like grammar books, English courses, or the internet to expand their knowledge of English grammar and to develop their writing ability. In line with that, it’s important for teachers to adopt innovative methods of teaching with detailed explanations to encourage students in learning, especially in writing degrees of comparison, to prevent the errors that occur in the future.